Respuesta :

Answer:

Step-by-step explanation:

The first step is to take p on both sides:

[tex]A - p = p + p*r*t - p[/tex]

On the right hand side, cancel p and -p, since [tex]p-p=0[/tex]. The equation will be:

[tex]A - p = p*r*t[/tex]

Then, divide both sides of the equation by p*t:

[tex]\frac{A-p}{p*t} = \frac{p*r*t}{p*t}[/tex]

On the right hand side, p*t can be cancelled:

[tex]\frac{A-p}{p*t} = r[/tex]

Answer:

r=A-p     (the line is the bar so this is a-p over pt)

    pt

Step-by-step explanation:

P + Prt = A

     

P r t=A −P            isolate the term which contains  r

   

P rt=A−P

divide pt by each side